On the subject of citizenship : late colonialism in the world tod ay - Pillay, Suren (London ; New York : Bloomsbury Academic, 2023)
"This volume brings together reflections on citizenship, political v iolence, race, ethnicity and gender, by some of the most critical voice s of our times. Detailed and wide-ranging individual reflections, take the writings of prominent Ugandan political theorist Mahmood Mamdani as a touchstone for thinking about the world from Africa. Contributors ap ply this theory to argue that we cannot make sense of the political con tentions of difference, identity and citizenship today without understa nding the legacies of colonial rule on our world. Chapters examine the persistence of the past, and how we must reckon with its tragedies, its injustices, and its utopias in order to chart a new politics; the poli tics of possible futures that are more inclusive and more egalitarian, and that can think of difference in more equitable ways. In a time when the call to decolonize knowledge, and politics rings loud and clear, t his is both a timely and a crucial intervention"--
Decolonizing the world : on Mamdani's thought / Kuan-Hsing Chen -- O f citizen(s) and subject(s) : Mamdani on research, methods, and commitm ents in postcolonial Africa / Siba N'Zatioula Grovogui -- Thinking with citizen and subject / Talal Asad -- Beyond the custom/market dichotomy : women's rights to land and the challenge of the commons / Nivedita M enon -- Empire in the era of DIY colonialism : barbarism or slavery in the (post)colonial context? / Abdelwahab El-Affendi -- The contemporary challenge of citizenship in Ethiopia and the role of empire in the mak ing of subject populations / Namhla Thando Matshanda -- Political ident ity and postcolonial democracy / Karuna Mantena -- Colonial legacies of ethnicized violence, gendered subjectivity, and feminist emancipatory politics / Lyn Ossome -- The bifurcated society : citizen and subject i n contemporary South Africa / Steven Friedman -- Predicaments of the co lonized : being coloured, Indian, and free after apartheid / Suren Pill ay -- The legacy of Bandung / Partha Chatterjee -- Looking back, lookin g forward / Mahmood Mamdani.
Includes bibliographical references and index.
Keywords: Mamdani, Mahmood, -- 1946-; Citizenship -- Africa; Political rights -- Africa; Postcolonialism -- Africa; Africa -- Colonial influence